Financial inclusion and economic uncertainty in developing countries: The role of digitalisation - Md. Jamil, Abd Rahim; Siong, Hook Law; Khair-Afham, Mohamad M.S.; Trinugroho, Irwan (Elsevier, 2023)
This study examines the nexus between financial inclusion and digitalisation on economic uncertainty and evaluates the moderation effect of digitalisation on the financial inclusion–economic uncertainty relationship. Two econometric techniques — generalised method of moments (GMM) estimators and quantile regression were employed to assess the relationship. We use a panel dataset of 73 developing countries representing lower-middle-income and upper-middle-income economies between 2004 and 2019. Our main findings from the GMM estimator reveal that digitalisation plays a role in increasing economic uncertainty. However, financial inclusion is an insignificant predictor of economic uncertainty in developing countries. Meanwhile, the interaction term between the financial inclusion and digitalisation variables on economic uncertainty is insignificant. This study also employs the panel quantile regression model to further explain the relationship. The result of quantile regression indicated that financial inclusion is vital in lessening economic uncertainty at the low quantile of economic uncertainty. Digitalisation also shows a significant positive relationship in both low and high quantiles, indicating that an upsurge in digitalisation is linked with a rise in economic uncertainty. Finally, we find a more substantial interaction effect in increasing economic uncertainty, especially in the low quantile distribution of economic uncertainty.